Residential care for those with neurological conditions: An exploration of three specialist neurological care facilities in the UK. (July 2013) - Wilson, Eleanor; Aubeeluck, Aimee
Abstract : Neurological conditions account for a high number of years lived with disability. Progressive long-term neurological conditions include Huntington's disease, Parkinson's disease, motor neurone disease, and multiple sclerosis. A multidisciplinary approach is recommended, but there is little evidence of the types of support needed for people living in long-term residential care facilities with these conditions. We used a qualitative case study approach to evaluate the care provided by three long-term residential care facilities. Focus groups ( n = 5), interviews ( n = 13), and observations were undertaken to engage 35 staff members, service users, and family members. Findings show an ethos of personalized and tailored care where continuity of staffing created a homely environment. Physical spaces were adapted to meet the needs of residents. On-site physiotherapy services were provided for all residents to proactively manage conditions and maintain as much function as possible. A range of social activities were also provided to engage residents in a variety of ways. These were felt to be delivered by dedicated staff members in specialist spaces and in consultation with residents. Participants based at the facilities reported high levels of specialist expertise. Findings from this evaluation highlight a number of areas of best practice. However, large-scale, longitudinal studies designed to capture measurable outcomes or provide cost–benefits analysis are now needed.